Rekomendasi Kebijakan Dukungan DPUTR Dalam Pengelolaan Sampah di DAS Citarum - Fauzana, Fauzana (JURNAL MOMEN TEKNIK SIPIL SURYAKANCANA, 2023)
Citarum River is the longest river in Province of West Java. Citarum River Basin covers 13 regencies/cities and 1.454 villages (Data RBI, 2018), consisting of 16 sub-basin spread across the upstream, middle, and downstream parts. Middle part of this basin crosses the north to middle part of Cianjur Regency. One of the problems in this basin is the presence of garbage which degrades river quality. In Cianjur Regency, solid waste management is the task of the Dinas LH (Environmental Service), but synergistic efforts between related departments is needed, including the PUTR (Public Works and Spatial Planning Office), so that solid waste problems can be handled optimally. By using the Readiness Criteria for Solid Waste Infrastructure, PUTR Office becomes a stakeholder for 2 criterias: conformity with spatial planning and adequate road access. This role can be carried out by actively coordinating spatial planning with the Dinas LH so that the location of solid waste infrastructure is in accordance with spatial planning and improving access (road infrastructure) to the Solid Waste Infrastructure to support waste transportation. In addition, there needs to be cooperation between the PUTR Office and the LH Service regarding the handling of solid waste that has entered water bodies. These roles need to be put into consideration in preparing budget plans in the Spatial Planning Implementation Program, the Water Resources Management Program, and the Road Implementation Program.